The Impact of Marketing Creativity as a mediating variable on the relationship between Marketing Efficiency and Market Positioning: An analytical study of the opinions of employees at Awamedica Pharmaceutical Company in Erbil - Azan Shreef, Ahmad; Nuri Abdullah, Mahabad (Iraqi Journal for Administrative Sciences, 2026)
The study aims to identify the levels of marketing efficiency and its dimensions (marketing costs, marketing development, communication and customer service, and customer satisfaction), as well as market positioning and its dimensions (product quality and safety, compliance and regulation, sustainability and social responsibility, and marketing capabilities), in addition to analyzing the impact relationship between them. The study also examined the effect of marketing creativity as a mediating variable, with its dimensions (product, pricing, promotion, and distribution), on the relationship between marketing efficiency and market positioning at Awamedica Pharmaceutical Manufacturing Company. The study adopted the descriptive-analytical approach and developed a hypothetical model of the relationships among the variables, which was subjected to several statistical tests using SPSS (Version 24). The study population consisted of 200 employees of the company. Due to the limited size of the population, a census sampling method was employed, whereby the research sample included all members of the population. A total of 200 questionnaires were distributed, of which 170 valid questionnaires were returned and suitable for statistical analysis. The study reached several conclusions, the most important of which is the existence of a statistically significant indirect effect of marketing efficiency on market positioning through marketing creativity. Among the key recommendations is the need to focus on developing new value-added products, innovating creative promotional campaigns, and enhancing effective distribution channels to strengthen the company’s market positioning.